2021
DOI: 10.1177/21582440211047559
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Evaluation Model for Monitoring Country-Based Tourism Competitiveness

Abstract: Using pillars and sub-index from the Travel and Tourism Competitiveness Index (T & TCI) to measure a destination’s competitiveness is popular. Still, its methodology underlying the calculation has been criticized. So the T&TCI Index has not been regarded as a reliable measure of a destination’s competitiveness. In this regard, this paper sought to set out a country-based tourism competitiveness evaluation model with various statistical methods to indicate how important tourism policy development has to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 109 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…The public factors are mainly determined by the following seven indicators: comprehensive tourism income; number of mountain tourist receptions; number of domestic tourist receptions; number of travel agencies; number of star-rated hotels; number of star-rated rooms; and A-score of tourist attractions. The revenue can be raised for specific tourism if more tourists visit there ( Liu et al, 2021 ). When tourism revenue grows faster, local tourism income rises, residents’ and staff’s income rises, local economic development improves, and the competitiveness of mountain-based other factors also rises ( Zeng et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The public factors are mainly determined by the following seven indicators: comprehensive tourism income; number of mountain tourist receptions; number of domestic tourist receptions; number of travel agencies; number of star-rated hotels; number of star-rated rooms; and A-score of tourist attractions. The revenue can be raised for specific tourism if more tourists visit there ( Liu et al, 2021 ). When tourism revenue grows faster, local tourism income rises, residents’ and staff’s income rises, local economic development improves, and the competitiveness of mountain-based other factors also rises ( Zeng et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Akin et al (2021), Armis and Kanegae (2021), Goffi andCucculelli (2019), Milićević et al (2020) and Neto et al (2020) indicated the ability to specify multilevel and reasonable prices of wellness tourism products and services were important factors. Dos Anjos and Da Rosa (2021), Ferreira and Perks (2020), Gajić et al (2018), Goffi and Cucculelli (2019), Liu et al (2021), Martín-González et al (2021, Mustafa et al (2021) and Neto et al (2020) showed that sustainable, environmentally friendly experiences could promote quality of life for people in the area were indicators of policies for attracting tourists. These findings align with Goal 7 of the SDGs, which focuses on affordable and clean energy .…”
Section: Discussionmentioning
confidence: 99%
“…They conclude that both of the offered techniques are reliable for estimating the T&TC of global tourist hotspots. Using the Tourist Competitiveness indicators from the World Economic Forum's (WEF) Trade and Competitiveness (T&TC) Index, Liu, Ko [52] planned to establish a country-based tourism competitiveness assessment model including the Kruskal-Wallis test and fuzzy AHP methodologies. Cultural distinctiveness and ecological/environmental considerations were selected as the two most important features by the group.…”
Section: Literature Review About Studies On Similar Methods and Subjectsmentioning
confidence: 99%